HUBUNGAN TINGGI BADAN DENGAN PANJANG KAKI PADA MAHASISWA FAKULTAS KEDOKTERAN UNSRAT - Paluta, Reniwaty S.; Tanudjaja, George N.; Pasiak, Taufiq F. (Jurnal Biomedik : JBM, 2013)
Abstract: Identification of a dead body is important in determining the clarity of one’s identity. Height is an important parameter in the process of identification and is one of the fields of study of physical anthropology. It is expected that the height can be determined by using the measurements of long bones, such as metatarsal bones and phalanges. This study aimed to find out the relationship between the height and foot length in the students of Faculty of Medicine University of Sam Ratulangi, Manado. This was a descriptive analytic study with cross-sectional design. Samples were selected by using systematic sampling methods. As samples, we used 74 students (registered in 2010) comprising 37 males and 37 females. Data were analyzed with a Pearson correlation analysis as well as a simple linear regression analysis. The results showed that there was a strong correlation between height and foot length with the correlation coefficients (r) of 0.846 for all samples, 0.520 for male students, and 0.711 for female students. The simple linear regression analysis resulted in three formulas: male height = 112.930 + 2.361 × foot length; female height = 4.223 + 64.241 × foot length; and overall height = 4.717 + 54.729 × foot length. Conclusion: There was a strong relationship between the heights and the foot lengths of students at the Faculty of Medicine University of Sam Ratulangi University Manado. Keywords: identification, height, foot length.   Abstrak: Identifikasi ialah pemeriksaan penting dalam menentukan kejelasan identitas seseorang. Tinggi badan merupakan parameter penting dalam proses identifikasi dan bidang telaah antropologi ragawi. Tinggi badan diharapkan dapat ditentukan dengan menggunakan pengukuran tulang-tulang panjang, diantaranya tulang metatarsal dan falang. Penelitian ini bertujuan untuk mengetahui hubungan antara tinggi badan dengan panjang kaki pada mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi Manado. Penelitian ini bersifat deskriptif analitik dengan rancangan cross-sectional. Sampel berjumlah 74 mahasiswa yang terdaftar pada tahun 2010, terdiri dari 37 laki-laki dan 37 perempuan. Sampel dipilih menggunakan cara systematic sampling. Data dianalisis dengan uji korelasi Pearson dan analisis regresi linier sederhana.  Hasl penelitian memperlihatkan terdapatnya hubungan kuat antara tinggi badan dan panjang kaki dengan koefisien korelasi (r) keseluruhan 0,846, pada laki-laki 0,520, dan pada perempuan 0,711. Dari hasil analisis regresi linier sederhana didapatkan rumus Tinggi Badan (TB) laki-laki = 112,930 + 2,361 × panjang kaki, TB perempuan = 64,241 + 4,223 × panjang kaki, dan secara keseluruhan TB = 54,729 + 4,717 × panjang kaki. Simpulan: Terdapat hubungan antara tinggi badan dan panjang kaki pada mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi Manado. Kata kunci: identifikasi, tinggi badan, panjang kaki.